PENGARUH MUSIK TERHADAP PERFORMANCE FISIK - Dedik S. Santoso (Institute of Research and Community Outreach - Petra Christian University, 2002)
The main objective of this study, as mentioned on the title, is to determine whether there is any effect of music on physical task performance. Three different kind of music were used in this study: easy listening/slow music, hard rock music, and subject's own favorite music. The same physical task without music was also conducted for every subject as the control. To simulate the physical task, each subject has to walk on a treadmill at a constant speed (3 MPH) and inclination (4º) for six minutes. Enough rest was given after a subject finished each task. Four undergraduate and six graduate students were volunteered as subjects in this study. They are three females and seven males. Statistical analysis software programs were used to analyze the results. It is shown from this study that slow music and favorite music have significant effect on the physical task. The heart rate is significantly lower when the subjects listened to a slow music or their favorite music while performing a physical task compared with performing the same task without listening to any music. The heart rate is not significantly different when subjects listened to hard rock music compared with no music listened. On the other hand, VO2 consumption is not significantly different between without music and with all kind of music. Therefore, according to this study, it is beneficial to listen to a certain kind of music while performing a physical task since they lower the heart rate. Abstract in Bahasa Indonesia : Tujuan utama dari paper ini adalah untuk menentukan apakah ada pengaruh dari musik terhadap performance dari seseorang saat melaksanakan pekerjaan fisik. Tiga jenis musik digunakan dalam studi ini: musik ringan, hard rock, dan musik favorit masing-masing subjek. Pekerjaan fisik yang sama tanpa musik juga dilaksanakan sebagai kontrol. Sebagai pekerjaan fisik, setiap subjek berjalan di atas treadmill dengan kecepatan konstan (4.8 km/jam) dan kemiringan konstan (4º) selama 6 menit. Setiap subjek diberikan istirahat yang cukup setiap kali selesai melaksanakan satu eksperimen. Sepuluh mahasiswa, tiga wanita dan tujuh pria berpartisipasi secara sukarela dalam studi ini. Program statistik digunakan untuk menganalisa hasil studi. Dari hasil perhitungan, tampak bahwa musik ringan dan favorit secara signifikan mempengaruhi performance fisik. Detak jantung per menit lebih rendah saat subyek mendengarkan musik ringan atau musik favorit mereka sambil melaksanakan pekerjaan fisik, dibandingkan tanpa mendengarkan musik. Pada saat mendengarkan musik hard rock, detak jantung menurun tetapi tidak signifikan. Di lain pihak, konsumsi oksigen tidak menurun secara signifikan bila tanpa musik dibandingkan dengan mendengarkan musik. Karena itu, akan lebih menguntungkan bila pada saat melakukan suatu pekerjaan fisik, pekerja mendengarkan musik ringan atau musik favorit mereka. Kata kunci: musik, performance fisik, detak jantung, konsumsi Oksigin